THE ROLE OF NURSING PRACTICE IN MODERN HEALTHCARE: CHALLENGES AND OPPORTUNITIES - Alimjonova Oynura Shukurali qizi (TADQIQOTLAR, 2025)
Abstract Nursing is a cornerstone of healthcare systems worldwide, playing a pivotal role in patient care, advocacy, and education. This paper explores the fundamental responsibilities of nurses, their contributions to healthcare delivery, and the challenges they face. It also emphasizes the importance of continuous professional development and policy support to enhance nursing outcomes globally.